Advances in the Molecular Genetics of Catecholaminergic Polymorphic Ventricular Tachycardia - Song, Junxia; Luo, Yanhong; Jiang, Ying; He, Jianfeng (Frontiers in Pharmacology, 2021)
Catecholaminergic polymorphic ventricular tachycardia is a primary arrhythmogenic syndrome with genetic features most commonly seen in adolescents, with syncope and sudden death following exercise or agitation as the main clinical manifestations. The mechanism of its occurrence is related to the aberrant release of Ca2+ from cardiomyocytes caused by abnormal RyR2 channels or CASQ2 proteins under conditions of sympathetic excitation, thus inducing a delayed posterior exertional pole, manifested by sympathetic excitation inducing adrenaline secretion, resulting in bidirectional or polymorphic ventricular tachycardia. The mortality rate of the disease is high, but patients usually do not have organic heart disease, the clinical manifestations may not be obvious, and no significant abnormal changes in the QT interval are often observed on electrocardiography. Therefore, the disease is often easily missed and misdiagnosed. A number of genetic mutations have been linked to the development of this disease, and the mechanisms are different. In this paper, we would like to summarize the possible genes related to catecholaminergic polymorphic ventricular tachycardia in order to review the genetic tests currently performed, and to further promote the development of genetic testing techniques and deepen the research on the molecular level of this disease.